Peran spiritualitas dalam meningkatkan emotional intelligence (eq) remaja - Gusni Putri, Tsabitah Aliyyah Aliyyah Gusni (Maliki Interdisciplinary Journal, 2026)
This study aims to examine the role of spirituality in enhancing emotional intelligence (EQ) among adolescents. Adolescence is a critical developmental stage marked by emotional fluctuations and identity exploration. Amid these challenges, spirituality functions as a guiding force that supports adolescents in building self-awareness, managing emotions, developing empathy, and fostering social responsibility. Using a qualitative descriptive approach through literature review, this study analyzes various scholarly sources to understand the connection between spiritual values and emotional development. The findings reveal that incorporating spiritual principles into adolescent life significantly strengthens self-control, deepens self-understanding, and contributes to positive character formation. Emotional intelligence, shaped through spirituality, becomes essential in social adaptation and responsible decision-making. Hence, spirituality is not solely a religious practice but also a foundational element in shaping emotionally intelligent and well-balanced individuals.